Relação entre avós, netos e escola: uma abordagem bioecológica. - Coelho, Maria Teresa Barros Falcão (2018)
The present study is based on the Bioecological Theory of Human Development and aims to investigate the relationship between guardian grandparents, grandchildren and school in this day and age, when several social changes affect the roles assumed by grandparents in raising their grandchildren, as well as the relationship they establish with one another and other development contexts. The thesis is structured in three interdependent studies. The first study, already published, corresponds to a systematic review of literature on grandparents raising grandchildren within a period of ten years (2004/2014). The results showed that, although the number of studies on the relationship between grandparents and grandchildren has increased in recent decades, researches regarding guardian grandparents are recent and still scarce, especially when investigating the relationship of grandparents with other development contexts, such as the school of their grandchildren. In order to accomplish the ensuing empirical studies, Ecological Insertion was used as the methodological strategy. Participants were selected intentionally, over an approach to a primary school of the state public school network in the city of Recife/Pernambuco. Diversified instruments were used over a period of eight months, total time of insertion of the researcher in the field. The first five months corresponded to the period of attachment of the researcher to the context, in which naturalistic observations were initiated. In the last three months sociodemographic questionnaires were applied and semi-structured interviews were conducted with the participants. The second study analyzes the relationship between guardian grandparents and their grandchildren from a bioecological perspective. Six guardian grandparents and eight grandchildren who answered sociodemographic questionnaires and semi-structured interviews were included in the study. From the Thematic Content Analysis, the following themes were discussed: grandparents’ parenting; joint activities that involve grandparents and grandchildren. The results showed that grandparents’ parenting is a relational process that is developed over time and involves individual and contextual dimensions. On the other hand, the analysis of joint activities revealed that guardian grandparents and grandchildren are primary dyads that influence and learn from each other in sports, leisure and cultural activities, corroborating with studies that affirm that such activities favor the creation and maintenance of the bond between grandparents and grandchildren. The importance of the intergenerational approach was discussed through intergenerational programs aimed at favoring coeducational processes that benefit grandparents and grandchildren. The third study analyzes the family and school mesosystem from the perspective of guardian grandparents, grandchildren and teachers. Six grandparents, eight grandchildren and eight teachers participated in this study. Semi-guided interviews (with a script for each group), field diary and sociodemographic questionnaire were used as instruments. In the analysis of the results, the sociodemographic data and the records of the observations were articulated to the contents brought by the participants in the interviews. All interviews were transcribed in full and analyzed according to the steps in Thematic Content Analysis. The following themes were discussed: the relationship between guardian grandparents and school; the ease and difficulties in that relationship; the information and communication between the family and the school contexts; and the joint activities involving family and school. In all these dimensions the obstacles and the possibilities for the expansion of the potential for development of the family and school mesosystem were analyzed. It was evidenced that important aspects to expand the potential for development of the family and school contexts were put into action with the presence of guardian grandparents in the school context by establishing a direct communication with the teachers, expecting the collaboration of the school in the development of their grandchildren, and suggesting actions and interventions. These results confirmed the growing importance of grandparents for family, school, and society as they play the role of guardians of their grandchildren.